Evaluation of functional aerobic exercise capacity among chronic e-cigarette users compared to combustible cigarette smokers and non-smokers: a comparative study - Heba Ammar; Rania Hashish; Shrouk Mohamed Ali; Ahmed Salem; Abeer Hagras (Bulletin of Faculty of Physical Therapy, 2023)
Abstract Background Electronic cigarettes or e-cigarettes have gained significant popularity as an alternative to traditional combustible tobacco smoking particularly among the youth. Although there is a growing prevalence of e-cigarette usage, the effects on cardiovascular function and physical capacity have not been adequately studied. The toxic products in combustible tobacco cigarettes negatively impact functional exercise capacity. However, the available data regarding the effect of e-cigarette use on functional exercise capacity are scarce. Thus, in the current study, we aimed to evaluate the functional aerobic exercise capacity among chronic e-cigarette users compared to combustible cigarette smokers and non-smokers. Results This comparative, cross-sectional study was conducted on 105 healthy volunteers. Participants were assigned into three study groups each consisting of 35 participants: chronic e-cigarette users, combustible cigarette smokers, and a non-smoker control group. Basal demographic and clinical data were similar in all groups. Mean heart rates and respiratory rates were significantly higher among e-cigarette smokers and combustible cigarette smokers compared to non-smoker controls (p < 0.001). Chronic e-cigarette users and combustible cigarette smokers had shorter 6-MWT distances compared to non-smokers (508.3, 488, and 616.6 m, respectively, p < 0.001). Borg scale scores after performing the six-minute walking test were significantly higher in chronic e-cigarette users and combustible cigarette smokers groups compared to non-smokers, where perceived exertion (4.9, 5.5, 2.1, respectively, p < 0.001), dyspnea (5.7, 6.5, 0.1, respectively, p < 0.001) and leg fatigue (4.2, 5.4, 1.4, respectively, p < 0.001). Conclusion In this cross-sectional study, significant evidence demonstrates that e-cigarette use is not harmless. This was particularly presented in apparently healthy e-cigarette users in comparison to the healthy non-smoker control group. Chronic e-cigarette use is associated with reduced functional capacity compared to non-smoker controls. This was signified by decreased 6MWT walking distances, higher Borg scale scores, and lower oxygen saturation percentages among the chronic electronic cigarette users as compared to non-smoker controls after performing the six-minute walking test. All the evaluated parameters in the current study were similarly reduced among both the e-cigarette users group and the combustible cigarette smokers group compared to non-smokers with no statistically significant differences between both smoker groups.